Analisis Implementasi Laravel 9 Pada Website E-Book Dalam Mengatasi N+1 Problem Serta Penyerangan Csrf dan Xss - M. Mahdi Maulana Lubis; Tommy; Divi Handoko; Nur Wulan (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
In the current digital era, the use of websites is increasing rapidly, people like everything that is instant, even in terms of reading books, they prefer to read e-books rather than reading books conventionally. Therefore we need a website that is able to process data quickly so that readers will not wait long when they want to find the book or journal they want. In addition, the website also stores data for readers and stores it, but there are lots of irresponsible people who use their data illegally, so further security is needed for the convenience of readers, therefore researchers will analyze the solution to website security problems from xss attacks. and csrf and N+1 problems using Laravel whether it has an effect on the e-book website or not at all